Research on land use structure optimization based on nonpoint source dissolved nitrogen load estimation in Shuaishui watershed - Lu, Yu-Chao; Bi, Meng-Fei; Li, Ze-Li; Sha, Jian; Wang, Yu-Qiu; Qian, Li-Ping (Huanjing kexue, 2014)
Regional Nutrient Management (ReNuMa) was applied to estimate dissolved nitrogen (DN) load and perform source apportionment in Shuaishui watershed during 2000-2010. Satisfactory performance of ReNuMa was revealed by the E(ns) and R2 of greater than 0.9 in calibrating and validating streamflow and DN. The average nonpoint DN load in this watershed was 1.11 x 10(3) t x a(-1), with the load intensity of (0.75 +/- 0.22) t x km(-2). Among all the land uses, paddy field had the largest DN load intensity [28.60 kg x (hm2 x a)(-1)], while forest had the least [2.71 kg x (hm2 x a)(-1)]. Agricultural land (including paddy, grain, cash crop, tea plant and orchard) contributed most to DN load in Shuaishui watershed, indicating that the human dominated agricultural activities was the major contributor of nonpoint source pollution. Land use structure optimization for Shuaishui watershed in 2015 was conducted under the rule of reducing pollutants loads and maximizing the agricultural output value. The results demonstrated t